Strategi dan Tantangan Komunikasi Organisasi dalam Membangun Kepercayaan antar Pemangku Kepentingan di Aceh Utara - Bustami; Syukur Kholil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
North Aceh is an area that has been hit by prolonged conflict, and still faces various challenges in building peace and stability. Trust between stakeholders, including government, civil organizations and society, is still fragile. Effective organizational communication can play an important role in building trust and cooperation between stakeholders to achieve common goals. This research uses qualitative methods with a case study in North Aceh. Data was collected through in-depth interviews with representatives from various organizations, including government, civil organizations and the community. This research found that various organizational communication strategies are used to build trust, such as open dialogue, information transparency, and active participation in decision making. However, there are several challenges faced, such as lack of resources, a culture of communication that is not open, and a history of conflict that still remains. Effective organizational communication can play an important role in building trust between stakeholders and achieving common goals. Addressing the challenges faced and implementing the recommendations in this research can help improve the effectiveness of organizational communications and build peace and stability in North Aceh. Keywords: Organizational Communication, Trust, Stakeholders